The effect of selective carious tissue removal and cavity treatments on the residual intratubular bacteria in coronal dentine - Pussadee Nakrathok; Kanittha Kijsamanmith; Kadkao Vongsavan; Praphasri Rirattanapong; Noppakun Vongsavan (Elsevier, 2020)
Background/purpose: The use of cavity treatments may help in the reduction of bacteria remaining in dentinal tubules after selective carious tissue removal. This study aimed to investigate the effect of selective carious tissue removal and treatment with either 35% phosphoric acid +0.12% chlorhexidine or dentine conditioner on the residual intratubular bacteria in coronal dentine of deep carious lesions. Materials and methods: Thirty carious human molars were randomly divided into three groups; group 1: untreated carious teeth (positive control), group 2: carious teeth treated with 35% phosphoric acid and chlorhexidine disinfectant after selective carious tissue removal and group 3: carious teeth treated with dentine conditioner after selective carious tissue removal. Another six non-carious teeth was used as negative control. The presence of bacteria and depth of bacteria remaining in dentinal tubules were determined by scanning electron microscopy (SEM). Chi square test and one-way, repeated-measures analysis of variance were used for statistical analysis. Results: Using SEM, coronal dentine of group 1, 2 and 3 revealed cocci, rod and filamentous bacteria within dentinal tubules. Positive rates of bacteria detection in coronal dentine of group 1 were significant higher than those of group 2 and 3 (P < 0.05). The distance of bacteria remaining in the dentinal tubules in group 1, 2 and 3 were 1149.14 ± 384.44, 707.98 ± 357.19 and 869.25 ± 470.75 μm, respectively. Conclusion: Both treatment groups had similar ability to reduce the number of intratubular bacteria in coronal dentine of carious teeth, but not complete elimination.